PENYULUHAN WASPADA INFEKSI ASCARIASIS PADA SISWA DAN SISWI SDN 1 SENGGIGI: Pendahuluan, Metode, Hasil dan Pembahasan, Simpulan dan Saran, Ucapan Terima Kasih - Rabbani, Muhammad Afif; Difa, Agung; Putri, Adelya Rahma; Madani, Ayda Fitri; Ramadhani, Dhea Asty; Triani, Eva (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
Ascariasis, a disease caused by roundworms, is one of the parasites that infects the human digestive system and represents a frequently occurring health issue among children, particularly in rural areas such as SDN 1 Senggigi. The objective of this research is to provide educational outreach about Ascariasis to the students of SDN 1 Senggigi as a preventive measure to reduce the risk of worm infections. This outreach encompasses information on the definition, life cycle, risk factors, transmission methods, symptoms, prevention, and treatment of Ascariasis. The educational approach involves presentations utilizing flip charts, along with practical demonstrations of hand and environmental hygiene. Research results indicate the effectiveness of this outreach in enhancing students’ knowledge about Ascariasis, accompanied by positive changes in knowing the definition, symptoms, transmission methods, prevention and treatment of ascariasis worms. With this increased awareness and knowledge, it is anticipated that the prevalence of Ascariasis infections in SDN 1 Senggigi will decrease and promote better health practices among children. Elevating awareness and education about this disease can also assist the broader community in addressing health issues, especially related to Ascariasis.